Indigenous perspectives on violence risk assessment: A thematic analysis - Shepherd, Stephane M. (Punishment & society, 2018)
Violence risk instruments are widely employed with at-risk minority clients in correctional and forensic mental health settings. However, the construction and subsequent validation of such instruments rarely, if at all, incorporate the perceptions, worldviews, life experiences, and belief systems of non-white communities. This study utilized a culturally informed qualitative approach to address the cross-cultural disparities in the forensic risk literature. Cultural perspectives on violence risk assessment were elicited from a sample of 30 American Indian and First Nations professionals from health, legal, and pedagogical sectors following an inspection of the Structured Assessment of Violence Risk in Youth instrument. Generally, participants believed that the Structured Assessment of Violence Risk in Youth instrument was not culturally appropriate for use with American Indian and First Nations youth in its current form. Recurrent themes of concern included the instrument’s negative labeling capacity, lack of cultural contextualization, individualized focus, and absence of cultural norms and practices. Recommendations to improve the cross-cultural applicability of the Structured Assessment of Violence Risk in Youth are discussed within.